Choroidal Neovascularization in Pediatric Patients: Analysis of Etiologic Factors, Clinical Characteristics and Treatment Outcomes - Zhang, Ting; Wang, You; Yan, Wenjia; Liu, Yafen; Lu, Jinglin; Sun, Limei; Li, Songshan; Huang, Li; Zhang, Zhaotian; Ding, Xiaoyan (Frontiers in Medicine, 2021)
Background and objectives: Choroidal neovascularization (CNV) is a common pathologic change that occurs in various chorioretinal diseases, but very limited published data have reported in pediatric patients. This study aimed to investigate the etiologic factors, clinical features, and treatment outcomes of choroidal neovascularization (CNV) in children. Methods: In this study, 33 eyes in 30 patients aged 18 years or younger with CNV were included. Comprehensive ophthalmic examination was performed in all the patients. The demographic profiles, laterality, visual acuity, optical coherence tomographic findings, fundus fluorescein angiographic findings, and the underlying pathology were analyzed. The types, locations, treatment outcomes, and recurrences of CNV were noted. Results: The average age was 11.2 ± 4.6 (range, 1–18) years. Most CNVs affecting children were classic and type 2. The most common etiologic factors of CNV in pediatric patients were congenital/developing abnormalities (9/30, 30.0%) and inflammatory retinochoroidopathy (9/30, 30.0%), followed by idiopathic CNV (8/30, 26.7%). Subtype analysis showed that the etiologic factor was inflammatory retinochoroidopathy in children 12 years or older, whereas congenital/developing abnormalities were present in children younger than 12 years. Eyes with active CNVs required a mean of 1.40 ± 0.58 injections. No recurrence was observed during follow-up. Conclusions: The etiologic factors of CNV in young Chinese patients were diverse, with congenital/developing abnormalities, inflammatory retinochoroidopathy and idiopathic CNV being the 3 most common ones. Eyes with active CNVs had good responses to antivascular endothelial growth factor treatment with low recurrence.